The prevalence of thyroid nodules and its factors among Chinese adult women: A cross-sectional study - Dong, Xiaoqian; Li, Ying; Xie, Jianfei; Li, Lijun; Wan, Ziyu; Kang, Yue; Luo, Yating; Wang, Jiangang; Duan, Yinglong; Ding, Siqing; Cheng, Andy SK (Frontiers in Endocrinology, 2022)
Objective: To determine the prevalence of thyroid nodules in Chinese adult women and the impact of lifestyle and metabolic syndrome on thyroid nodules as well as their predictors. Methods: We conducted a cross-sectional study in the tertiary hospital from 2017 to 2019. Included participants underwent thyroid color Doppler ultrasonography, lipids examination, and dietary evaluation. Results: Totally, 933 thyroid nodules patients and 1,851 individuals without thyroid nodules were included. The prevalence of thyroid nodules was 33.3%. Women in 50-59 years (OR: 1.746, 95% CI [1.356-2.249]), older than 60 (2.147 [1.540-2.993]) and occupations with mainly manual work (1.780 [1.367-2.317]) were risk factors for thyroid nodules, while moderate dietary diversity (0.624 [0.476-0.817]) and normal triglycerides level (0.739 [0.604-0.905]) were protective factors. Conclusion: Women over 50 and those whose jobs are mainly manual should enhance screening, follow-up and health management of thyroid nodules. Higher dietary diversity is protective measures against thyroid nodules for adult women and should consider dietary balance and the food varieties, not just increased quantities.